PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE RECIPROCAL TEACHING TERHADAP HASIL BELAJAR SISWA PADA MATERI LOGIKA DI SMA NEGERI 5 PADANGSIDIMPUAN - Sari, Mutia; Harahap, Yuni Efrina (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2018)
This study aims to see the influence of the use of cooperative learning model type reciprocal teaching on the learning outcomes of students of logic material in class X of SMA Negeri 5 Padangsidimpuan. This study uses an experimental method with non-equivalent design (untreated control group design with pretest and posttest). The results of the data analysis requirements test obtained by both classes of samples were normally distributed and homogeneous. The t-test results of the learning results obtained are t_ (count) = 2.936 t_ (table) = 2.016, so that there is a rejection of H_0 and acceptance of Ha. This means that there is the effect of using the cooperative learning model type reciprocal teaching on student learning outcomes in the logic material at Padangsidimpuan 5 High School.